THE IMPORTANCE OF ENERGY FOR THE ECONOMY, SUSTAINABLE DEVELOPMENT AND ENVIRONMENTAL PROTECTION - AN ECONOMIC ASPECT - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2018)
In the area of ​​modern economy and environmental protection there are no significant changes: the old problems are not solved, and the existing ones are deepening. Humanity is still struggling with three existential problems: lack of food, lack of drinking water and insufficiently energized energy. They are also associated with the dangers of further degradation of the environment, the general fear and fear of terrorism and wars, the emergence of diseases for which modern medicine simply has no solution and which threatens to overcome the challenge of pandemic. Energy is still a mood of economic development, with at the same time a disastrous effect on the environment, when traditional sources of fossil resources are used as sources of energy. The paper explores the phenomenon of the impact of energy on the sustainable development of the economy, with a key focus on environmental protection, as well as the possibilities for adaptation to mitigate the consequences of this global phenomenon. In this regard, special attention has been devoted to researching the role and significance of energy from renewable sources as a possible response to current or expected climate stimuli or their consequences in natural and humanism systems. Particular emphasis is placed on the principle of adaptation, which includes mitigation of damages or the exploitation of effective opportunities; understanding how climate can change, what can be impacts, and capacity building and action on these impacts.